In their own words: Experiences of emergency health care workers during the COVID‐19 pandemic. (22nd May 2022) - Blanchard, Janice; Messman, Anne M.; Bentley, Suzanne K.; Lall, Michelle D.; Liu, Yiju Teresa; Merritt, Rory; Sorge, Randy; Warchol, Jordan M.; Greene, Christopher; Diercks, Deborah B.; Griffith, James; Manfredi, Rita A.; et al.
Abstract: Background: During the COVID‐19 pandemic, a substantial number of emergency health care workers (HCWs) have screened positive for anxiety, depression, risk of posttraumatic stress disorder, and burnout. The purpose of this qualitative study was to describe the impact of COVID‐19 on emergency care providers' health and well‐being using personal perspectives. We conducted in‐depth interviews with emergency physicians, emergency medicine nurses, and emergency medical services providers at 10 collaborating sites across the United States between September 21, 2020, and October 26, 2020. Methods: We developed a conceptual framework that described the relationship between the work environment and employee health. We used qualitative content analysis to evaluate our interview transcripts classified the domains, themes, and subthemes that emerged from the transcribed interviews. Results: We interviewed 32 emergency HCWs. They described difficult working conditions, such as constrained physical space, inadequate personnel protective equipment, and care protocols that kept changing. Organizational leadership was largely viewed as unprepared, distant, and unsupportive of employees. Providers expressed high moral distress caused by ethically challenging situations, such as the perception of not being able to provide the normal standard of care and emotional support to patients and their families at all times, being responsible for too many sick patients, relying on inexperienced staff to treat infected patients, and caring for patients that put their own health and the health of their families at risk. Moral distress was commonly experienced by emergency HCWs, exacerbated by an unsupportive organizational environment. Conclusions: Future preparedness efforts should include mechanisms to support frontline HCWs when faced with ethical challenges in addition to an adverse working environment caused by a pandemic such as COVID‐19.